Factors affecting nectar sugar composition in chiropterophilic plants - Nelly Rodríguez-Peña; Kathryn E. Stoner; Cesar M. Flores-Ortiz; Jorge Ayala-Berdón; Miguel A. Munguía-Rosas; Víctor Sánchez-Cordero; Jorge E. Schondube (Revista Mexicana de Biodiversidad)
Most pollinators prefer the sugars present in the nectar they consume, so it has been hypothesized that they have molded nectar trait evolution. However, nectar-feeding bats do not exhibit preferences for the sugars present in their diet. We analyzed the role that biochemical and ecological factors could play in shaping the nectar traits of chiropterophilic plants. We studied nectar traits and flower production in 49 plant species. We evaluated the relationship between nectar concentration and sugar composition using phylogenetically independent contrasts and if nectar traits were related to flower production using a Manova. We found that 42 species produced high hexoses nectars, and 7 species produced sucrose rich nectars. Phylogenetically independent contrasts showed that nectar concentration was negatively related to glucose content, positively related to fructose content, and was not related to sucrose content. A negative relationship was found from glucose and fructose contents to sucrose content, and glucose content was negatively related to fructose content. Finally, we did not found any relationship between nectar traits and the plants’ flowering strategies. We conclude that bat physiology and the relative low evolutionary time of the interaction between plants and bats may determine the lack of pattern in the nectar characteristics of chiropterophilic plants.